fyqt.net
当前位置:首页 >> 3.4x 26.8 >>

3.4x 26.8

3.4x-48=26.8 3.4X=26.8+48 3.4X=74.8 X=74.8÷3.4 X=22

3.4*减48加48=26.8加48

3.4X-48=26.8 3.4X=74.8 X=22

解: 3.4X-48=26.8 => 3.4X=26.8+48 => 3.4X=74.8 => X=74.8/3.4 => X=22 答:X=22

3.4x-48=26.8 3.4x=26.8+48 3.4x=74.8 x=74.8/3.4 x=22

解:3.4x-48=26.8 3.4x=74.8 x=22

解:3.4x=26.8+48 x=74.8÷3.4 x=22

3/4X-3/8=1.75 3/4X=3/8+1.75 3/4X=17/8 X=17/8*4/3 X=17/6

21+4x=25 4x=25-21 x=4/4 x=1

3.8+x=6.3 x=6.3-3.8 x=2.5 x-7.9=2.6 x=2.6+7.9 x=10.5 2.5x=14 x=14/2.5 x=5.6 x÷3=1.2 x=3.6 3.4x-48=26.8 3.4x=26.8+48 3.4x=74.8 x=22 2x-97=34.2 2x=34.2+97 2x=131.2 x=65.6 42x+25x=134 67x=134 x=2

网站首页 | 网站地图
All rights reserved Powered by www.fyqt.net
copyright ©right 2010-2021。
内容来自网络,如有侵犯请联系客服。zhit325@qq.com